Umbilical cord-matrix stem cells induce the functional restoration of vascular endothelial cells and enhance skin wound healing in diabetic mice via the polarized macrophages - Zhang, Shichang; Chen, Li; Zhang, Guoying; Zhang, Bo (Stem cell research & therapy, 2020)
Chronic nonhealing wounds represent one of the most common complications of diabetes and require advanced treatment strategies. Increasing evidence supports the important role of mesenchymal stem cells in diabetic wound healing; however, the underlying mechanism remains unclear. Here, we explored the effects of umbilical cord-matrix stem cells (UCMSCs) on diabetic wound healing and the underlying mechanism. UCMSCs or conditioned medium (UCMSC-CM) were injected into the cutaneous wounds of streptozotocin-induced diabetic mice. The effects of this treatment on macrophages and diabetic vascular endothelial cells were investigated in vivo and in vitro. Our results reveal that UCMSCs or UCMSC-CM accelerated wound healing by enhancing angiogenesis. The number of host macrophages recruited to the wound tissue by local infusion of UCMSCs was greater than that recruited by fibroblast transplantation or control. The frequency of M2 macrophages was increased by UCMSC transplantation or UCMSC-CM injection, which promoted the expression of cytokines derived from M2 macrophages. Furthermore, when cocultured with UCMSCs or UCMSC-CM, lipopolysaccharide-induced macrophages acquired an anti-inflammatory M2 phenotype characterized by the increased secretion of the cytokines interleukin (IL)-10 and vascular endothelial growth factor and the suppressed production of tumor necrosis factor-α and IL-6. UCMSC-CM-activated macrophages significantly enhanced diabetic vascular endothelial cell functions, including angiogenesis, migration, and chemotaxis. Moreover, the action of UCMSC-CM on macrophages or vascular endothelial cells was abrogated by the administration of neutralizing antibodies against prostaglandin E2 (PGE2) or by the inhibition of PGE2 secretion from UCMSCs. Our findings demonstrate that UCMSCs can induce the functional restoration of vascular endothelial cells via the remodeling of macrophage phenotypes, which might contribute to the marked acceleration of wound healing in diabetic mice.